Preliminary study on the effect of commercially available eye toners on rabbit corneal keratocytes proliferation and migration - Mohamad Sukri, Norhamiza; Razali, Rabiatul Adawiyah; Arifin, Nurfadzillah; Harun, Nurul Athirah; Mohd Azid @ Nazid, Ruwaida; Suboh, Ruzira; Mohamad Sofian, Nurul Damia; Abdul Rahman, Suzanah; Abdul Rahim, Muhd Afzam Shah; Sha'ban, Munirah (Tissue Engineering and Regenerative Medicine Society of Malaysia, 2015)
Devoid of scientific proofs, the use of commercially available natural product-based eye toners for therapeutic purposes incites controversies surrounding it. This study aims to evaluate the effect of selected commercially available eye toners on in vitro cellular model using rabbits’ corneal keratocytes. The primary cells were cultivated in culture media supplemented with or without eye toners as control. Growth kinetic profile, cells proliferation assay, scratch assay and immunocytochemistry analysis were performed in comparing both culture media. There were no significant differences between control and the commercially available eye toners in the growth kinetics and cell proliferation. Microscopic observation of the scratch assay suggested the eye toners did not promote cells migration as compare to control. However, in the immunohistochemistry study the eye toners are able to sustain the expression of Connexin-43 and Lumican. This preliminary study indicates that the selected eye toners do not promote the proliferation and migration of corneal keratocytes. They are able to maintain the expression of Connexin-43 and Lumican which might have beneficial effect in corneal transparency. Studies with individual element of the eye toners need to be done.